Village-Based Common Pool Resource Management: Clean Water Management to Overcome Water Crisis Problems in Prambanan Hills - Kusumawati, Felinda; Abisono, Fatih Gama (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
This study examines the management of common pool resources in the context of clean water management by the village. This research departs from the lack of water availability for Prambanan residents who live in hilly areas, this is especially true when entering the dry season. The purpose of this study is to explain that the village is the right institution for managing shared resources or common pool resources where the Village Government and Water User Management Organizations (OPPA) are the factors that determine the success of using common pool resources in meeting clean water needs for the community. With the method of collecting data through observation, interviews, and documentation related to the required data. This research is qualitative research, with the study method being a qualitative case study. Based on the results of research and data analysis obtained, some of the efforts that have been made by the Government cannot be said to be effective and are not a solution to overcome the drought problem in Kapanewon Prambanan hilly areas but after the management is handed over to the village the distribution of water becomes more even for the community. In conclusion, in the management of shared resources or common pool resources, villages are the right institutions to manage shared resources or common pool resources because they are distributed more evenly to the community and can improve the welfare of the village community itself. With the management of clean water by the village, the burden of the government in overcoming the drought problem in the community can be overcome.